How senior leaders support innovations in large learning health systems: Insights from United States Veterans Health Administration national program office leaders - Jaifred Christian F. Lopez; Sallie Allgood; Kate Sheahan; Brandolyn White; M. Amy Kirshner; Suzanne Shirley; Madison Coffey; Amanda Milo; Sarah L. Cutrona; Laura Damschroder; Gemmae M. Fix; Andrea L. Nevedal; et al. (Learning Health Systems)
Abstract Background The U.S. Veterans Health Administration (VHA) formed an Innovation Ecosystem that develops and disseminates innovative practices to enhance Veterans' health. Support of senior leadership and their perception of the innovation process is key to the Ecosystem's success. We aimed to elicit insights on (1) how national VHA program office leaders define innovation, and (2) important considerations in facilitating the adoption of innovations. Methods As part of a quality improvement initiative, we conducted 19 semi‐structured interviews via teleconference. Interviews involved 4 administration offices, 7 clinical and population health program offices, and 8 policy and quality improvement offices; 12 of these offices reported experience working with the Innovation Ecosystem. Responses were audio recorded, transcribed, and analyzed using constructs from the Consolidated Framework for Implementation Research. Results Participants generally agreed that innovation within VHA is defined by evidence‐based development and implementation of interventions that improve response to Veterans' needs. Considerations in facilitating innovations include: (1) implementation climate that promotes network‐building, open communication, and well‐executed planning processes; (2) implementation infrastructures that enable engagement with key players and augment existing resources; and (3) innovation evidence strength and responsiveness to patient needs. Individuals working in policy‐related offices were more likely to identify complexity, leadership engagement, culture and available resources as factors in choosing innovations to adopt. Individuals who reported experience of working with the Ecosystem emphasized the importance of intra‐organizational networks and a favorable implementation climate, while those without experience noted the importance of working with external change agents. CFIR ‘inner setting’ constructs were seen in responses across all categories; meanwhile, emerging constructs highlight how innovation should be balanced by the reality of operations. Conclusions Among national VHA program office leaders, innovation is pursued to improve Veterans' health. Resources, networks, culture, and processes are considered important factors among program office leaders to support and encourage innovation.